Modeling the Conduction Mechanism in Chemoresistive Gas Sensor Based on Single-Crystalline Sn3O4 Nanobelts: A Phenomenological In Operando Investigation - Suman, Pedro H. [UNESP]; Junker, Benjamin; Weimar, Udo; Orlandi, Marcelo O. [UNESP]; Barsan, Nicolae (American Chemical Society (ACS), 2024)
Investigating the sensing mechanisms in semiconducting metal oxide (SMOx) gas sensors is essential for optimizing their performance across a wide range of potential applications. Despite significant progress in the field, there are still many gaps in comprehending the phenomenological processes occurring in one-dimensional (1D) nanostructures. This article presents the first insights into the conduction mechanism of chemoresistive gas sensors based on single-crystalline Sn3O4 nanobelts using the operando Kelvin Probe technique. From this approach, direct current (DC) electrical resistance and work function changes were simultaneously measured in different working conditions, and a correlation between the conductance and the surface band bending was established. Appropriate modeling was proposed, and the results revealed that the conduction mechanism in the single-crystalline one-dimensional nanostructures closely aligns with the behavior observed in single-crystalline epitaxial layers rather than in polycrystalline grains. Based on this assumption, relevant parameters were further estimated, including Debye length, concentration of free charge carriers, effective density of states in the conduction band, and position of the Fermi level. Overall, this study provides an effective contribution to understanding the role of surface chemistry in the transduction of the electrical signal generated from gas adsorption in single-crystalline one-dimensional nanostructures.
Keywords: conduction mechanism; gas sensing; one-dimensional nanostructures; semiconducting metal oxide (SMOx); single-crystalline nanobelts; Sn3O4; tin oxide